Specialty coffee expansion in traditional retail: lessons from non-traditional retailers - Rosenblum, Alison (Kansas State University, 2015)
Despite at least three waves of transformations in the US coffee retail market, traditional retailers have not altered their merchandizing approaches for decades. This may be due primarily to the fact that there are still margins being made in selling canned coffee, the initial coffee wave in this research. Yet, because of their significant role in the retail segment, traditional retailers cannot be ignored by coffee suppliers. This implies that with each shift in the coffee industry, it is important for the participants to find ways of enabling the traditional retailer to make the necessary transformation – at least with their products – so that they can secure their market share and their continuing success. The research develops a number of case studies of different coffee retailers who are developing innovative processes for merchandizing new coffee formats, such as Keurig K-Cups and Ready to Drink (RTD) products. The research shows that coffee merchandizers can learn from these retailers to develop support programs for their traditional retail customers to leverage their importance in the coffee market to enhance their own sales and profitability. We identify a number of value innovation strategies that may be used to achieve this objective of enhancing performance in traditional coffee merchandizing. For example, we identify a store-within-a store strategy that is already in operation for a number of product categories in traditional retail, and suggest that it be expanded to include coffee. This approach will elevate purchases across the segment and help enhance overall competitiveness. The approach is not unlike Kroger’s treatment of its natural and organics as a separate department or Roche Brothers’ creation of a gourmet specialty, which is prominently displayed near the store’s entry. It has become a prime location where new and exciting entrants to the specialty assortment are presented to shoppers in an elevated way. In this location, they are typically expected to sell-through initial quantities rapidly. The research presents innovative ideas to help coffee purveyors help their customers reposition emerging “waves” of coffee products in their traditional retail systems. It hopes that traditional retailers will benefit from the case studies of lessons from other categories and initiatives so that they can improve their own performance, and in so doing help coffee purveyors enhance their own performance.
Keywords: Retail trade; Merchandising; Coffee; Starbucks; ERIC Model; Economics, Agricultural (0503); Economics, Commerce-Business (0505); Marketing (0338)